National study of the prevalence of gestational diabetes mellitus among Danish women from 2004 to 2012. Issue 8 (December 2017) - Jeppesen, Charlotte; Maindal, Helle T.; Kristensen, Jette K.; Ovesen, Per G.; Witte, Daniel R.
Aims: The prevalence of gestational diabetes mellitus (GDM) is increasing worldwide. We studied the prevalence of GDM from 2004 to 2012 in Danish women aged 15–49 years using registries with records of the diagnosis of GDM at delivery. Methods: We conducted a national register-based study of 12, 538 women with a diagnosis of GDM during a pregnancy leading to a live birth in the period 2004–2012. The diagnosis of GDM was taken from the National Patient Registry and combined with the total number of births at the national level from Statistics Denmark. Prevalence estimates were reported as crude and age-standardized using Danish and international data for women aged 15–49 years. Results: A total of 566, 083 live births was registered in Denmark from 2004 to 2012. The age-standardized prevalence of GDM increased from 1.7% (1095/63, 465) of the total births in 2004 to 2.9% (1721/56, 894) of the total births in 2012. During the period 2004–2012, the age-stratified prevalence increased from 1.1 to 1.8% among women aged 15–24 years, from 1.5 to 2.6% among women aged 25–34 years and from 2.9 to 4.7% among women aged 35–49 years. The prevalence was higher among immigrants and their descendants than in native Danish women (4.06 and 2.09% in 2007 vs. 4.51 and 2.72% in 2012, respectively). Conclusions: The prevalence of GDM in Denmark has increased across all age groups. Although the prevalence is low on a global scale, attention should be paid to this development by preventive health services.